Zintegrowany pomiar rentowności i płynności firmy jako narzędzie symulacji planów finansowych - Kowalczyk, Jacek (The Integrated Liquidity and Profitability Measurement as a Tool for Financial Plans Simulation, 2005)
Separate analyses containing individual ratios used in the evaluation do not show the relation between financial occurrences, especially between liquidity and profitability. The structural systems of ratios are much better way of measurement. The report gives examples of building different ratio-systems, which contain liquidity and profitability. Those ratio-systems can be used to evaluate different variants of financial plans and also to analyze the sensibility of financial plans.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 190-200